THE MEDIATING INFLUENCE OF NARRATIVE TRANSPORTATION ON AUDIENCE INTEREST IN INSTAGRAM MARKETING CONTENT - Ratnawati; Sebastian; Yopita (Department of Management - Institut Shanti Bhuana, 2026)
Digital storytelling has emerged as a vital strategy in social media marketing to attract and retain audience interest, particularly on Instagram. This study investigates the mediating role of narrative transportation in the relationship between digital storytelling, emotional engagement, and audience interest. A quantitative approach was employed, with data collected through purposive sampling from 100 active Instagram users in Indonesia. Path analysis was used to test the proposed model using SPSS software. The findings reveal that both digital storytelling and emotional engagement influence audience interest, with narrative transportation acting as a significant mediating variable. Specifically, narrative transportation enhances the effect of emotional engagement on audience interest (R² increases from 0.083 to 0.271) and partially mediates the effect of digital storytelling (indirect effect = 0.252). Although the direct effect of digital storytelling on narrative transportation was not statistically significant, its impact on audience interest becomes more meaningful when narrative immersion is present. These results confirm that immersive narrative experiences can convert emotional responses into meaningful audience engagement. The study contributes to the theoretical understanding of Narrative Transportation Theory in digital marketing and offers practical insights for creating emotionally compelling and narratively immersive Instagram content to boost audience interest.